New refiners for permutation group search. (May 2019) - Jefferson, Christopher; Pfeiffer, Markus; Waldecker, Rebecca
Abstract: Partition backtrack is the current generic state of the art algorithm to search for subgroups of a given permutation group. We describe an improvement of partition backtrack for set stabilizers and intersections of subgroups by using orbital graphs. With extensive experiments we demonstrate that our methods improve performance of partition backtrack – in some cases by several orders of magnitude.